THE EFFECT OF ACADEMIC SUPERVISION AND PRINCIPAL’S LEADERSHIP ON TEACHERS’ PERFORMANCE IN THE ELEMENTARY SCHOOL IN EAST JAKARTA - Rachmatul UMMAH; Fitria Yeni BAHRI (Journal of Education and Leadership in Education, 2020)
The purpose of this research was to investigate the effect of academic supervision to teachers’ performance; the effect of headmaster’s leadership to teachers’ performance; and the effect of academic supervision, headmaster’s leadership simultaneously to teachers’ performance. This quantitative research employed a survey method to find out the effect of researched variables. Multiple regression analysis was employed to test the effect of three variables. 200 elementary school teachers in east Jakarta participated in filling the questionnaire. The research has revealed that (1) academic supervision affects teachers’ performance positively and significantly; (2) the principal's leadership affects teacher's performance positively and significantly; (3) academic supervision and school principal leadership affect teachers’ performance positively and significantly.